Analysis and Approximate Replacement of Tool for Trapezoid Spline Shaft - Zhigang Cao; Jianzhong Xu; Guangjun Shao; Kun Zhang; Shaobo Kang; Yakang Li; Hechen Xing; Yu Zhao; Shaofei Wang (Jixie chuandong)
The trapezoid spline has the characteristics of good guidance and self-centering， and its application range has been extended to the field of low-speed and high-torque transmission. Based on the tooth profile normal line method， the formula of the hob tooth profile of the trapezoid spline shaft is analyzed. At the same time， the formula for the cross-sectional shape of the forming cutter is derived. Finally， the tooth profile deviation of the involute spline shaft instead of the trapezoid spline shaft is calculated. It will provide a certain reference for the actual use and localization of related parts.